2017
DOI: 10.3382/ps/pex087
|View full text |Cite
|
Sign up to set email alerts
|

Fowl adenovirus serotype 4: Epidemiology, pathogenesis, diagnostic detection, and vaccine strategies

Abstract: Fowl adenovirus (FAdV) serotype-4 is highly pathogenic for chickens, especially for broilers aged 3 to 5 wk, and it has emerged as one of the foremost causes of economic losses to the poultry industry in the last 30 years. The liver is a major target organ of FAdV-4 infections, and virus-infected chickens usually show symptoms of hydropericardium syndrome. The virus is very contagious, and it is spread both vertically and horizontally. It can be isolated from infected liver homogenates and detected by several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 92 publications
1
57
0
Order By: Relevance
“…Thus, we believe that FAdV, CIAV and LaSota play respective but related roles in vivo, increasing one another’s pathogenicity in complex interactions. FAdV-4 could damage the liver, decrease protein synthesis function, reduce plasma colloid osmotic pressure, and finally increase the exudative tendency [ 30 ]. Meanwhile, the decrease of erythrocytes caused by CIAV not only substantially lowered the oxygen transport capacity of blood, induced hypoxia and compensatory rise of angiosthenia but also could cause strong immunosuppression [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we believe that FAdV, CIAV and LaSota play respective but related roles in vivo, increasing one another’s pathogenicity in complex interactions. FAdV-4 could damage the liver, decrease protein synthesis function, reduce plasma colloid osmotic pressure, and finally increase the exudative tendency [ 30 ]. Meanwhile, the decrease of erythrocytes caused by CIAV not only substantially lowered the oxygen transport capacity of blood, induced hypoxia and compensatory rise of angiosthenia but also could cause strong immunosuppression [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…FAdVs are non-enveloped, double-stranded DNA viruses [ 2 ] of poultry that are capable of causing hydropericardium-hepatitis syndrome (HHS), inclusion body hepatitis (IBH), or gizzard erosion (GE), resulting in significant economic losses to the poultry industry all over the world [ 3 , 4 , 5 ]. Almost all of the pathogenic FAdVs can induce IBH with or without mortality [ 6 , 7 , 8 , 9 ], whereas fowl adenovirus serotype 4 (FAdV-4) plays a primary role in the etiology of HHS, with mortality varying from 10 to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Fowl adenovirus serotype-4 (FAdV-4) is a member of the Aviadenovirus genus, Adenoviridae family, and contains non-enveloped and double-stranded DNA with a genome of approximately 43–46 kb that encodes 11 non-structural proteins [E1A, E1B, E2A (DBP), E3 (ADP), E4, EP, 33 K, 52/55 K, pol, pIVaII, and 100 K] and 10 primary structural proteins (hexon, penton base, fiber, terminal protein, protein μ, protein IIIa, protein V, protein VI, protein VII, and protein VIII; Griffin and Nagy, 2011 ; Xie et al, 2013 ; Li et al, 2017 ). This virus can cause acute avian infectious diseases such as hydropericardium hepatitis syndrome (HHS), inclusion body hepatitis (IBH), and gizzard erosion in duck layers and broilers (Marek et al, 2012 ; Chen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, severe outbreaks of HHS have occurred in commercial duck farms in Jiangsu, Anhui, Hubei, Jiangxi, Shandong, and Henan Provinces, China, resulting in high mortalities, pericardial effusion, and stunted growth among ducks (Chen et al, 2016 ; Yu et al, 2018 ). Several previous studies have focused on the epidemiology (Liu et al, 2015 ; Zhang et al, 2016 ; Li et al, 2017 ), gene structure (Mase et al, 2009 ; Griffin and Nagy, 2011 ; Shah et al, 2016 ), diagnostic detection (Günes et al, 2012 ; Junnu et al, 2014 ; Niczyporuk et al, 2015 ; Wang et al, 2017 ), and vaccine strategies (Schonewille et al, 2010 ; Shah et al, 2012 , 2017 ) for the disease. Unfortunately, little is known about the pathogenicity of this virus in Cherry Valley meat ducks, except that intracerebral infection caused a 15% mortality rate (Chen et al, 2016 ) and oral infection showed no clinical signs (Pan et al, 2017 ); therefore, to complete the pathogenicity of the virus, Cherry Valley meat ducks were infected with FAdV-4 in this study.…”
Section: Introductionmentioning
confidence: 99%